Fighting Cheating in P2P-based MMVEs with Disjoint Path Routing - Schuster, Sebastian; Wacker, Arno; Weis, Torben (Electronic Communications of the EASST, 2009)
In a P2P-based Massively Multiuser Virtual Environment (MMVE) where nodes cannot be trusted, replicating data on multiple nodes is a possibility to increase the reliability to obtain correct data. Current structured P2P networks mostly place replicas in such a way that queries for the replicas travel along similar paths. A malicious node in the common part of all paths can nullify the security gain of replicated data. We therefore propose to combine radix-based prefix routing with a symmetric replication scheme to gain disjoint paths to each of the replicas.